Soxhlet and High-Pressure Processing (HPP) Method: Antimicrobial Study on the Chromolaena odorata and Azadirachta indica Leaves Extracts Against Six (6) Opportunistic Bacteriast Six (6) Opportunistic Bacteria - Nur Helwa Kamaruszaman; Muhammad Faiz Razali; Sity Aishah Mansur; Angzzas Sari Mohd Kassim; Aliff Hisham A. Razak; Hariz Haikal Nasuha; Noor Akhmazillah Mohd Fauzi (Journal of Science and Technology, 2024)
Chromolaena odorata and Azadirachta indica are well-known for their antimicrobial properties and have long been utilized in traditional medicine for treating various skin ailments. This study aimed to compare the efficacy of two extraction methods, Soxhlet extraction and High-Pressure Processing (HPP), in extracting bioactive components from C. odorata and A. indica, and their resulting antimicrobial activity. The antimicrobial properties of the extracted samples were assessed using the Kirby-Bauer disc diffusion method and minimum inhibitory concentrations (MICs). The maximum inhibition zones against E. coli were observed for Soxhlet-extracted C. odorata (17.25 mm) and A. indica (16.67 mm). The MICs were recorded as 0.78% for C. odorata and 3.13% for A. indica, which were notably higher than those of the HPP extracts. For the HPP extracts, treatment at 600 MPa for 10 minutes showed lower MICs against E. coli, with values of 100.0% and 12.5% for C. odorata and A. indica, respectively. Overall, the antimicrobial activity of the Soxhlet-extracted samples was significantly greater than that of all HPP samples. Although Soxhlet extraction demonstrated higher antimicrobial activity, HPP offers advantages as an efficient herb extraction method due to its ability to extract essential compounds from C. odorata and A. indica in a short period and its non-thermal nature, which reduces the degradation of bioactive chemicals. Therefore, these findings hold significant promise, particularly in the cosmeceutical and health product sectors, where the potential of C. odorata and A. indica as natural antimicrobial agents and wound healers could contribute to minimizing harm to human health.